Ethanol extract of Neem (azadirachta indica a. juss) twigs peel gel increased neovascularization, fibroblast and epithelialization in wound healing of male albino Wistar rats (Rattus norvegicus) - Noviyanti Situmorang; I Gusti Made Aman; Ni Nyoman Ayu Dewi (Fakultas Kedokteran Universitas Udayana, 2020)
Introduction: Proper wound healing is characterized by increased neovascularization, fibroblast cell number and epithelialization. This process can be accelerated using several natural substances and one of them is Neem (Azadirachta indica A. Juss) twigs extract. However, its wound healing effect is still poorly investigated. Therefore, the aim of this study was to assess the efficacy of ethanol extract of Neem twigs peel gel toward wound healing in male albino Wistar rats (Rattus norvegicus). Methods: A randomized posttest only control group study was conducted using 28 male albino Wistar rats as a subject. Subjects were divided into four groups; the first and second group was the control group which was treated using placebo gel for 4 and 12 days while the third and fourth groups were treated with 12.5% extract gel for 4 and 12 days. On day 4 and 12, rats were euthanized then examined histologically. Results: The results showed a significant increase of neovascularization in the P1.4 compared to P0.4. However, it decreased significantly at day 12. Similarly, the number of fibroblast cells was also increased in the treatment group until day 4 but decreased significantly and even lower than the control group at day 12. On contrary, epithelialization was continuously increased in both group and the treatment groups consistently demonstrated higher epithelialization compared to control. Conclusion: It can be concluded that ethanol extract of Neem twigs peel gel enhanced wound healing process in male albino Wistar rats.